SIFAT FISIKA DAN MEKANIKA KAYU REPEH (Mangifera gedebe Miq.) (Physical and Mechanical Properties of Repeh (Mangifera gedebe Miq.)) - Isna Yuniar Wardhani (Tengkawang : Jurnal Ilmu Kehutanan, 2011)
Repeh (Mangifera gedebe Miq.) is one of lesser known species that does not utilize optimally yet because of lacking data of this wood species. Repeh wood has been used by rural people in East Kalimantan traditionally as housing material such as wall. The purpose of this research is to determine the fresh moisture content, density and static bending strength of Repeh based on DIN standard. Four logs of Repeh taken from Kutai Kartanegara District as sample and divided into three parts. The data was display by graphic. The result showed that the average of fresh moisture content and density are 102,21% and 0,46 g/cm, whereas MOE is 7428 N/mm and MOR is 51,2 N/mm. According to MOE and MOR, Repeh including to Wood Strength Class IV III and it could be as light construction material and furniture. Keywords: Repeh, fresh moisture content, density, static bending strength